Utilization of Instagram as a Marketing Media (Case Study of Online Buying Services @my_shopper.id) - Kharismatul Ula, Elok (Lafadz Jaya Publisher, 2022)
The rapid development of the world of information and communication has made changes in the world of marketing, one of which is the existence of social media marketing. Various social media platforms are now provided including TikTok, Line, WhatsApp, YouTube and so on. Instagram is no exception, which is used as a marketing medium by the courier service (jastip) @my_shopper.id. The purpose of this study is to find out the use of Instagram as a marketing medium for the courier service business @my_shopper.id. A service for depositing branded goods such as clothes, bags, perfumes and others. The research method uses a qualitative descriptive type to clearly know the information from the jastip account owner regarding the use of Instagram social media as a marketing tool. Data collection is carried out by in-depth interviews with account owners, then collects documentation by capturing content layers used in Instagram accounts. Data analysis uses Miles and Huberman, namely by data reduction, data presentation and verification. Test the validity of the data using triangulation techniques for conducting interviews and collecting documents to informants. The results of the study indicate that the surrogate service account (jastip) @my_shopper.id does social media marketing through an Instagram account. Account owners use various available features such as comment fields, Instagram bio, Instagram traffic, feeds, reels. The content created also varies such as product photos, product review videos, uploading customer testimonials to uploads regarding the order packaging process. The use of Instagram as a marketing medium has the advantage of increasing traffic and making people know about this jastip. Weaknesses obtained include missing information, sometimes customers do not know branded products and entrusting services.